Social Media Marketing Influencer: Literature Review on Promotional Strategies Using the Influence of Social Media Celebrities - Nadia Angraini (International Journal of Economic Research and Financial Accounting, 2023)
Social media marketing influencer is one of the digital marketing promotion strategies that is known to be very effective in approaching consumers. This research is a literature review study that aims to discuss more deeply about social media marketing by using celebrity influencers as their online marketing communication in approaching potential consumers. Researchers take international articles from the data base of publishers Elsevier, Scopus and emerald that are in accordance with the study studied. From the articles that researchers have obtained, reviews are carried out to take important points about influencer social media marketing information. The result of this study is that promotional strategies that use celebrity influencer social media marketing are known to be more influential than other celebrities, because consumers feel more intense and feel close to the daily activities of celebrity influencers on social media. This research contributes as one of the literatures that discusses the study of digital marketing in social media and is expected to be a reference for readers and other researchers who want to examine the study of the same phenomenon regarding digital marketing promotion strategies using social media influencers.